Evaluation of uranium incorporation from contaminated areas using teeth as bioindicators - a case study - Prado, G. R.; Arruda-Neto, J. D. T.; Sarkis, J. E. S.; Geraldo, L. P.; Mueller, R. M. L.; Garcia, F.; Bittencourt-Oliveira, M. C.; Guevara, M. V. Manso; Rodrigues, G.; Mesa, J.; Rodrigues, T. E. (Oxford University Press, 2008)
The Southwest region of the Bahia state in Brazil hosts the largest uranium reserve of the country (100 kton in uranium, only), plus the cities of Caetite, Lagoa Real and Igapora. In this work, aim was at the investigation of uranium burdens on residents of these cities by using teeth as bioindicators, as a contribution for possible radiation protection measures. Thus, a total of 41 human teeth were collected, plus 50 from an allegedly uranium free area (the control region). Concentrations of uranium in teeth from residents of 5- to 87-y old were determined by means of a high-resolution inductively coupled plasma mass spectrometer (ICP-MS). The highest uranium concentration in teeth was measured from samples belonging to residents of Caetite (median equal to 16 ppb). Assuming that the uranium concentrations in teeth and bones are similar within 10-20% (for children and young adults), it concluded that uranium body levels in residents of Caetite are at least one order of magnitude higher than the worldwide average. This finding led to conclude that daily ingestion of uranium, from food and water, is equally high.